Self-determined motivation and types of sportive cooperation among players on competitive teams: a Bayesian network analysis - Ponseti, F. J.; Garcia-Mas, A.; Palou, P.; Cantallops, J.; Fuster-Parra, P. (International Journal of Sport Psychology, 2016)
The aim of this study was to analyse the relationship between levels of selfdetermined motivation and the factors of sportive cooperation in young sports players. 270 athletes belonging to official competitive teams were studied, from the Balearic Islands, Spain (M = 14.6; Range = 11-18; SD = 1.53). To this end, we used the Behavioral Regulation in Sport Questionnaire and the Cuestionario de Cooperación Deportiva. The relationships of probabilistic dependence and independence of the six variables studied were established using a validated Bayesian network. Afterward, hypothetical probability values of the variables of cooperation were instantiated to observe changes in the probabilities in levels of self-determination. The results indicate that unconditional cooperation and extrinsic motivation are the most probabilistically independent variables, with intrinsic motivation being directly dependent on the other two. Conditional cooperation and amotivation have the lowest probability values in the athletes studied. The main conclusion is that cooperation and extrinsic motivation are the two roots of team dynamics, as unrelated variables. Coaches should take advice on that fact regarding their coaching style.